Belang and Kabata Banda; The significance of nature in the "adat" practices in the Banda Islands - Donkersgoed, Joëlla van; Farid, Muhammad (Wacana, Journal of the Humanities of Indonesia, 2022)
As an island community, the culture of the Bandanese is closely linked to their natural maritime environment. Not only is fishery the main source of income for many Bandanese, their cultural practices also include the creation of traditional boats and songs which tie the people, their environment and history together. These boats, locally referred to as belang or kora-kora, feature symbolic decorations and take part in an annual competition in which competing villages chant about their oral stories, known as kabata. Before this performance, various sacred locations, keramat, are honoured and a ceremony is held at the traditional house in which special bamboo poles play a central role in the performance of the cakelele warrior dance. This article highlights how nature plays a significant role in the traditional practices of the villages in the Banda Islands and illuminates certain passages from kabata in which Bandanese nature is honoured in song.